Identifying Predictors of Cumulative Healthcare Costs in Incident Atrial Fibrillation: A Population‐Based Study. Issue 4 (April 2015) - Bennell, Maria C.; Qiu, Feng; Micieli, Andrew; Ko, Dennis T.; Dorian, Paul; Atzema, Clare L.; Singh, Sheldon M.; Wijeysundera, Harindra C.
Abstract : Background: Atrial fibrillation (AF) has substantial impacts on healthcare resource utilization. Our objective was to understand the pattern and predictors of cumulative healthcare costs in AF patients after incident diagnosis in an emergency department (ED). Methods and Results: Patients discharged after a first presentation of AF to an ED in Ontario, Canada, were identified from April 1, 2005, through March 31, 2010. Per‐patient cumulative healthcare costs were determined until death or March 31, 2012. Join‐point analyses identified clinically relevant cost phases. Hierarchical generalized linear models with a logarithmic link and gamma distribution determined predictors of cost per phase. Our cohort was 17 980 patients. During a mean follow‐up of 3.9 years, 17.1% of patients died. Three distinct cost phases were identified: 2‐month post–index ED visit phase, 12‐month predeath phase, and a stable/chronic phase. The mean cost per patient in the first month post–index ED visit was 1876 (95% CI 1822 to 1931), 8050 (95% CI 7666 to 8434) in the month before death, and 640 (95% CI 624 to 655) per month for the stable/chronic phase. The main cost component in the post‐index phase was physician services (32% of all costs) and hospitalizations for the predeath phase (72% of all costs). The CHA2 DS2 ‐VASc clinical risk score was a strong predictor of costs (rate ratio 1.91 and 5.08 for score of 7 versus score of 0 in predeath phase and postindex phase, respectively). Conclusions: There are distinct phases of resource utilization in AF, with highest costs in the predeath phase.